2016
DOI: 10.1038/srep28005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among People Living with HIV and AIDS in China: Implications for Enhancing Linkage

Abstract: To assess the patterns and predictors of AIDS-related mortality and identify its correlates among adult people living with HIV/AIDS (PLWHA) in China, a retrospective record-based cohort study was conducted among 18 years or older PLWHA, who had at least one follow up reported to the national database between January-1989 and June-2012. Cumulative Incidence Function was used to calculate AIDS-related mortality rate. Gray’s test was used to determine the variation in cumulative incidence across strata. The Fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…In an era where effective and free testing and free treatment options are available in China, it is alarming that there is a substantial proportion of people were late diagnosed, and they are at higher risk of early death. A records-based retrospective cohort study in China found that the highest mortality rates for AIDS-related death and all-cause death were found in the first year of follow up after HIV diagnosis [ 52 ]. This phenomenon could be explained by the fact that about half of the participating cases had already progressed to AIDS before being identified, progression to AIDS was one of the strongest risk factors for AIDS-related death, with an aHR of 7.42 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an era where effective and free testing and free treatment options are available in China, it is alarming that there is a substantial proportion of people were late diagnosed, and they are at higher risk of early death. A records-based retrospective cohort study in China found that the highest mortality rates for AIDS-related death and all-cause death were found in the first year of follow up after HIV diagnosis [ 52 ]. This phenomenon could be explained by the fact that about half of the participating cases had already progressed to AIDS before being identified, progression to AIDS was one of the strongest risk factors for AIDS-related death, with an aHR of 7.42 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the HIV epidemic has continued to expand, and the mortality attributable to HIV/AIDS has become a major public health concern[6]. In July 2017, approximately 728,270 persons were living with HIV/AIDS in China, and 223,798 died from AIDS-related illnesses[7].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, an increased mortality of HIV and AIDS was detected in the present study. We speculate that the increase of HIV and AIDS mortality may be partially explained by the accumulation of AIDS cases, since the cumulative AIDS-related mortality rates significantly increased over time after diagnosis [31]. Meanwhile, the inadequate provision of treatment services and difficulty with adherence were also likely to contribute to the increased mortality, particularly before 2003.…”
Section: Discussionmentioning
confidence: 95%